Utilization of Educational Technology in Islamic education - Supiana; Asep Sumarna; Elva Siti Fatimah; Qiqi Yuliati Zaqiah (EDUTEC : Journal of Education And Technology, 2024)
ABSTRACT The integration of information and communication technology in education is driving the acceleration of computer literacy in Indonesian society. This research uses a qualitative approach with a descriptive study method. The focus of this research relates to the application of technology in PAI learning at Alfa Centauri Elementary School, Bandung. To obtain the data used is by interview, observation, and documentation. Furthermore, the data were analyzed using data reduction, data presentation, and drawing conclusions. The validity of the data is obtained through data triangulation technical tests. The results of research on technological advances have led to many changes, including in the field of education which gave birth to the concept of e-learning. With e-learning, learning becomes more effective and efficient. The integration of information and communication technology in primary school education improves the quality of education in these institutions. Keywords: Technology; Education; Islam.